Development of a population pharmacokinetic–pharmacodynamic model of a single bolus dose of unfractionated heparin in paediatric patients - Al‐Sallami, Hesham (Br J Clin Pharmacol, 2016)
BACKGROUND: Unfractionated heparin (UFH) is the anticoagulant of choice in paediatric patients undergoing a variety of cardiac procedures. There are currently no population pharmacokinetic–pharmacodynamic (PKPD) models for UFH in paediatrics. OBJECTIVE: The aim of the present study was to develop and evaluate a PKPD model of UFH in paediatrics. METHODS: Data from 64 children who received 75–100 IU kg(−1) of UFH during cardiac angiography were analysed. Five blood samples were collected at baseline and at 15, 30, 45 and 120 min postdose. The UFH concentration was quantified using a protamine titration assay. The UFH effect was quantified using activated partial thromboplastin time (aPTT). A PKPD model was fitted using nonlinear mixed‐effects modelling. Patient covariates such as gender, weight (WT) and fat‐free mass (FFM) were tested. The final model was evaluated using the likelihood ratio test and visual predictive checks (VPCs). RESULTS: A one‐compartment model with linear elimination provided the best fit for the dose–concentration data. FFM was a significant covariate on clearance. A linear model provided the best fit for the concentration–effect data using aPTT as a biomarker for effect. The models performed well using VPCs. However, when used to simulate UFH infusion (at a much lower dose), the model overpredicted target aPTT responses. CONCLUSIONS: A PKPD model to describe the time course of the UFH effect was developed in a paediatric population. FFM was shown to describe drug disposition well. However, when applied to smaller UFH infusion doses, the model overpredicted target aPTT responses. This unsuccessful extrapolation may be attributed to a possible nonlinear relationship for heparin PKPD.